Searching for air showers with RNO-G - Henrichs, Jakob; Aguilar, Juan A.; Allison, Patrick; Besson, Dave; Bishop, Abigail; Botner, Olga; Bouma, Sjoerd; Buitink, S.; Cataldo, Maddalena; Clark, B. A.; Couberly, K.; Curtis-Ginsberg, Z.; et al. (Proceedings of Science, 2023)
The Radio Neutrino Observatory - Greenland (RNO-G) is an in-ice neutrino detector, using radio emission to target the first measurement of neutrinos beyond PeV energies. In total 35 stations are planned for the detector, resulting in a detection volume of around 100 km3. Each of these stations is equipped with deep antennas embedded ∼ 100 m into the ice and downward-pointing log-periodic dipole antennas (LPDA) buried ∼ 3 m into the snow. At each station, three additional buried LPDA are pointing towards the sky and thus can be used to look for cosmic-ray induced air-showers. These air showers are a background for the RNO-G detector and therefore important to understand, but they also can be used as a calibration tool. In order to find the air-shower signals, we apply an analysis based on template matching to the data. We present the current status of the analysis targeting the detection of cosmic-rays induced air showers. This includes the presentation of a method to create a complete template set and a first look at RNO-G data.
CRIS-Team Scopus Importer:2023-12-15